Chronic Exposure to Perfluorooctane Sulfonate Induces Behavior Defects and Neurotoxicity through Oxidative Damages, In Vivo and In Vitro - Chen, Na (Public Library of Science, 2014)

(untitled) (PLoS One)
Perfluorooctane sulfonate (PFOS) is an emerging persistent pollutant which shows multiple adverse health effects. However, the neurotoxicity of PFOS and its mechanisms have not been fully elucidated. Using a combination of in vivo and in vitro methods, the present study provides a detailed description of PFOS-induced neurotoxicity. Results showed that the median lethal concentration of PFOS was 2.03 mM in Caenorhabditis elegans for 48 h exposure. 20 µM PFOS caused decrease of locomotor behaviors including forward movement, body bend and head thrash. Additionally, PFOS exposure reduced chemotaxis index of C. elegans, which indicates the decline of chemotaxis learning ability. Using green fluorescent protein (GFP) labelled transgenic strains, we found that PFOS caused down-regulated expression of a chemoreceptor gene, gcy-5, in ASE chemosensory neurons, but did not affect cholinergic neurons and dopaminergic neurons. In SH-SY5Y cells, 48 h exposure to 25 µM and 50 µM PFOS induced cell damage, apoptosis and the reactive oxygen species (ROS) generation. PFOS caused significant increases of lipid peroxidation and superoxide dismutase activity, but an actual decrease of glutathione peroxidase activity. Furthermore, antioxidant N-acetylcysteine rescued cells from PFOS-induced apoptosis via blocking ROS. Our results demonstrate that chronic exposure to PFOS can cause obvious neurotoxicity and behavior defects. Oxidative damage and anti-oxidative deficit are crucial mechanisms in neurotoxicity of PFOS.